2013
DOI: 10.1038/nn.3548
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation in sound localization: from GABAB receptor–mediated synaptic modulation to perception

Abstract: Across all sensory modalities, the effect of context-dependent neural adaptation can be observed at every level, from receptors to perception. Nonetheless, it has long been assumed that the processing of interaural time differences, which is the primary cue for sound localization, is nonadaptive, as its outputs are mapped directly onto a hard-wired representation of space. Here we present evidence derived from in vitro and in vivo experiments in gerbils indicating that the coincidence-detector neurons in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 49 publications
11
80
0
Order By: Relevance
“…Although previous single-unit studies in mammals reported contralateral tuning centered around ±90°, our spatial tuning measures derived from the BOLD responses show a rearward shift in contralateral tuning (e.g., ± 90°−120°). While LI shifts toward more rear sound positions could potentially be due to the expectancy of subsequent sound sources (Stange et al, 2013), they are in accordance with previous population measures of neuronal tuning in awake monkey AC (Woods et al, 2006). Interestingly, shifts in amplitude tuning around the midline were drastic as compared to rear midline sectors indicating a sharp slope tuning in frontal space as compared to rear sound positions, which suggest a potential different mechanism for coding backward space.…”
Section: Discussionsupporting
confidence: 89%
“…Although previous single-unit studies in mammals reported contralateral tuning centered around ±90°, our spatial tuning measures derived from the BOLD responses show a rearward shift in contralateral tuning (e.g., ± 90°−120°). While LI shifts toward more rear sound positions could potentially be due to the expectancy of subsequent sound sources (Stange et al, 2013), they are in accordance with previous population measures of neuronal tuning in awake monkey AC (Woods et al, 2006). Interestingly, shifts in amplitude tuning around the midline were drastic as compared to rear midline sectors indicating a sharp slope tuning in frontal space as compared to rear sound positions, which suggest a potential different mechanism for coding backward space.…”
Section: Discussionsupporting
confidence: 89%
“…We add another advantage; v i,d and v c,d may be individually adjustable, creating additional degrees of freedom that may allow for more precise matching of ipsilateral and contralateral delays. We note also that delay may also be adjusted on a faster time scale, through mechanisms other than regulation of latency (Stange et al 2013). Further discussion of this and related topics may be found in recent reviews (Grothe et al 2010).…”
Section: Robustness Regarding Possible Reconstruction Errorsmentioning
confidence: 72%
“…This is important, because even though we do not know what other internal delays may be generated in the circuit, inhibition can provide additional timing shifts that largely span the distribution of gerbil ITD functions recorded in vivo (Fig. 8b)67843, which has been thus far unsuccessful by axon length disparity-based models of ITD tuning11. Interestingly, at timing conditions where inhibition is most capable of influencing coincidence detection, IPSPs would largely be masked by EPSPs, which is compatible with the in vivo observation that even at low frequencies IPSPs remained undetected between cycles8.…”
Section: Resultsmentioning
confidence: 99%